719 Effects of Physical Activity on Patients With Diabetes Type 2: A Systematic Review (Balneo and PRM Research Journal, 2024)
The aim of the research was to collect and to examine the positive effects of various physical activity (PA) programs on individuals with type 2 diabetes mellitus (T2DM). This included a combination of aerobic exercises and resistance training, with varying intensities, in order to compare which approach yielded better outcomes for T2DM management; This systematic review was conducted in line with PRISMA guidelines, focusing on the period from 1991 to 2024. Studies included in this review involved both experimental procedures and questionnaire-based surveys to assess the impact of PA on T2DM patients. The primary outcome was the effect of PA on T2DM, with secondary outcomes including changes in blood pressure, cholesterol levels, and glycemic control; A total of 23 studies, encompassing 1752 participants (515 men, 546 women, and 691 unspecified), met the inclusion criteria. The studies highlighted the positive effects of exercise, such as improvements in glycemic control, insulin sensitivity, and lipid profiles. Most studies recommended a combination of aerobic and resistance exercises performed 3-4 times per week for 30-60 minutes per session; This systematic review confirms that regular PA is instrumental in managing T2DM. Health care providers should integrate PA programs into treatment plans for T2DM patients to optimize glycemic control and overall health outcomes.